The Northern Sea Route as a New Route for Maritime Transport between the Far East and Europe - Andrej Dávid; Andrea Galieriková; Jiří Tengler; Vlatka Stupalo (Communications - Scientific letters of the University of Zilina, 2021)
Asian countries such as China, Malaysia, India or Bangladesh belong to the largest producers of consumer goods in the world that is mainly transported by container vessels to other parts of the world. One of the busiest maritime trade route is the route between Europe and Asia. It leads through the North Pacific, Indian and the North Atlantic Oceans and their seas. There is also an alternative trade route that runs along the coast of the Russian Federation across the Arctic Ocean. On one hand the ice in this area is gradually declining due to global warming, on the other hand the duration of navigation times is being extended for several months of the year. One of the advantages of this route is the reduction of sailing times between Asian and European maritime ports. The basic goals of the paper are to focus on the current transport situation on this trade route and a new trade route that leads along the coast of Russia.